2018
DOI: 10.1016/j.ymthe.2018.08.018
|View full text |Cite
|
Sign up to set email alerts
|

Upregulation of lncRNA ADAMTS9-AS2 Promotes Salivary Adenoid Cystic Carcinoma Metastasis via PI3K/Akt and MEK/Erk Signaling

Abstract: Neurotropic infiltrative growth and distant metastasis are the main causes of death in salivary adenoid cystic carcinoma (SACC) patients. Long noncoding RNAs (lncRNAs) are involved in many human neoplasms, however, their potential roles in SACC are unclear. In our study, we found that ADAM metallopeptidase with thrombospondin type 1 motif, 9 (ADAMTS9) antisense RNA 2 (ADAMTS9-AS2) was significantly upregulated in SACC patients with metastasis and SACC-lung metastasis (LM) cells. Moreover, ADAMTS9-AS2 expressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
63
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(64 citation statements)
references
References 41 publications
1
63
0
Order By: Relevance
“…[25][26][27][28][29] And abnormal expression of PI3K-Akt signaling pathway has been found to play an important role in the diagnosis and prognosis of gastric cancer. In recent years, a large number of studies have found that the PI3K-Akt signaling pathway is involved in important functions such as growth, differentiation, proliferation, invasion, and metastasis of gastric cancer cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[25][26][27][28][29] And abnormal expression of PI3K-Akt signaling pathway has been found to play an important role in the diagnosis and prognosis of gastric cancer. In recent years, a large number of studies have found that the PI3K-Akt signaling pathway is involved in important functions such as growth, differentiation, proliferation, invasion, and metastasis of gastric cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…In gliomas, ADAMTS9-AS2 acts as a novel tumor suppressor that inhibits glioma cell metastasis. [25][26][27] The PI3K-Akt signaling pathway is involved in important functions such as growth, differentiation, invasion, and metastasis of gastric cancer cells. 23 In ovarian cancer, ADAMTS9-AS2 affects the progression of ovarian cancer by targeting the miR-182-5p/FOXF2 signaling pathway.…”
Section: Relationship Between Lncrnamentioning
confidence: 99%
“…lncRNAs located in the cytoplasm are usually associated with post-transcriptional regulation. 20,26 To identify DANCR-interacting proteins in BCa cells, we performed RNA pull-down assays using in vitro-transcribed biotinylated DANCR. One overtly differential band between 130 and 150 kDa appeared after silver staining, and it was identified as LRPPRC by mass spectrometry ( Figure 4C; Figure S3A).…”
Section: Dancr Directly Interacts With Lrpprc To Play Key Roles In Bcamentioning
confidence: 99%
“…The PARIS Kit purchased from Invitrogen (Carlsbad, CA, USA) was applied to isolate cytoplasmic and nuclear RNAs using a previously established protocol, followed by RT-qPCR detection [15]. Total RNA from OSCC tissues and cells was collected using the TRIzol Reagent (Invitrogen Life Technologies) and was subsequently reverse transcribed to cDNA using the PrimeScript RT reagent Kit (Takara, Tokyo, Japan).…”
Section: Subcellular Fraction and Real-time Quantitative Pcr (Rt-qpcr)mentioning
confidence: 99%